Hematological Profile of Women in Pregnancy in a Hilly District of Himachal Pradesh - Sharma, Anuj; Vohra, Jai Gopal; Behal, Manisha; Bansal, Sneha (Indian Journal of Community Health, 2020)
Introduction: Anemia during pregnancy is a major public health problem throughout the world, especially in the developing countries. Anemia during pregnancy can lead to morbidity and mortality in mother as well as fetus. Anemia cannot be diagnosed only clinically, several blood tests are required for complete characterization. Aim of the present study was to know the prevalence of anemia during pregnancy in District Solan of Himachal Pradesh, classify its types and determine the effect of pregnancy on hematological parameters in Anemia. Material and Methods:In the present study Hematological parameters of 150 pregnant females in advanced pregnancy (of gestational age 32 to40 weeks) were analyzed and the results were compared with 90 age matched control cases. Results: The pregnant study group exhibited statistically significant lower values of haemoglobin, PCV, MCV, MCHC and lymphocyte and platelets while neutrophil and total WBC counts were significantly elevated. Conclusion: Hematological parameters are a simple and cost effective investigation which can aid in early recognition of anemia during pregnancyand thereby improve the outcome of pregnancy.